The Effect Of Sekadi In Diabetic Ulcer Risk Patients On Abi Score - Nila Duni Aura Syifa; Maulida Nurfazriah Oktaviana; Rizki Mega Safitri (PROFESSIONAL HEALTH JOURNAL, 2025)
Diabetic ulcers are a feared complication of type 2 diabetes, characterized by damage or loss of the skin layer in the epidermis, tendons, muscles, bones, or joints. The issue of diabetic ulcers in Banyuanyar village, Kalibaru, involved 30 respondents. This research aims to identify the presence of peripheral artery disease using the Ankle Brachial Index (ABI), analyze changes in ABI after diabetic foot exercises are performed on patients at risk of diabetic ulcers, and identify changes in the Ankle Brachial Index (ABI) before and after the diabetic foot exercises. This research is a quantitative study with a quasi-experimental design using a one-group pre-test post-test approach. The sample consists of 30 respondents, and the sampling technique used is purposive sampling. Data collection was carried out using a research instrument in the form of ABI scores to determine the presence of PAD disease. The research results were statistically tested using the Wilcoxon test, with a p-value of 0.000 < α (0.05), which means there is a relationship between before and after the SEKADI was conducted. The respondents are hoped to perform SEKADI independently.